A community proposal to integrate structural bioinformatics activities in ELIXIR (3D-Bioinfo Community) - Orengo, Christine; Velankar, Sameer; Wodak, Shoshana; Zoete, Vincent; Bonvin, Alexandre M J J; Elofsson, Arne; Feenstra, K Anton; Gerloff, Dietland L; Hamelryck, Thomas; Hancock, John M; Helmer-Citterich, Manuela; Hospital, Adam; et al. (F1000Research, 2020)
Structural bioinformatics provides the scientific methods and tools to analyse, archive, validate, and present the biomolecular structure data generated by the structural biology community. It also provides an important link with the genomics community, as structural bioinformaticians also use the extensive sequence data to predict protein structures and their functional sites. A very broad and active community of structural bioinformaticians exists across Europe, and 3D-Bioinfo will establish formal platforms to address their needs and better integrate their activities and initiatives. Our mission will be to strengthen the ties with the structural biology research communities in Europe covering life sciences, as well as chemistry and physics and to bridge the gap between these researchers in order to fully realize the potential of structural bioinformatics. Our Community will also undertake dedicated educational, training and outreach efforts to facilitate this, bringing new insights and thus facilitating the development of much needed innovative applications e.g. for human health, drug and protein design. Our combined efforts will be of critical importance to keep the European research efforts competitive in this respect. Here we highlight the major European contributions to the field of structural bioinformatics, the most pressing challenges remaining and how Europe-wide interactions, enabled by ELIXIR and its platforms, will help in addressing these challenges and in coordinating structural bioinformatics resources across Europe. In particular, we present recent activities and future plans to consolidate an ELIXIR 3D-Bioinfo Community in structural bioinformatics and propose means to develop better links across the community. These include building new consortia, organising workshops to establish data standards and seeking community agreement on benchmark data sets and strategies. We also highlight existing and planned collaborations with other ELIXIR Communities and other European infrastructures, such as the structural biology community supported by Instruct-ERIC, with whom we have synergies and overlapping common interests.
Keywords: Instruct-ERIC; Proteins; nucleic acids structure; biologické vědy; genomika; ELIXIR; Computational Biology; protein structure; Humans; biomolecular structure; Genomics; lidé; proteiny; Biological Science Disciplines; Europe; Evropa; structural bioinformatics; výpočetní biologie